THE MEDIATION ROLE OF MOTIVATION ON THE INFLUENCE OF COMMUNICATION, BUDGET PARTICIPATION, AND COMPENSATION ON MANAGERIAL PERFORMANCE - Resma Frederika; Nining Asniar Ridzal (Journal Economics Technology And Entrepreneur, 2025)
This study aims to analyze the effect of communication, budget participation, and compensation on managerial performance through motivation as a mediating variable in Regional Apparatus Organizations (OPD) in South Buton Regency Government. The research method used was a quantitative survey approach. Primary data were obtained by distributing questionnaires to 108 respondents, consisting of OPD employees. Data analysis was conducted using SPSS using validity and reliability tests, multiple linear regression, and mediation tests. The results showed that: (1) communication had no significant effect on managerial performance; (2) budget participation has a positive and significant effect on managerial performance; (3) compensation had a positive and significant effect on managerial performance; (4) motivation was able to mediate the relationship between communication and managerial performance. (5) Motivation also mediates the relationship between budgetary participation and managerial performance; however, (6) motivation does not mediate the relationship between compensation and managerial performance. This finding confirms the important role of participation and a fair compensation system in improving the managerial performance of local government officials